(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To establish relevance between low back pain and transitional vertebra at lumbosacral junction. Research Design: was qualitative, descriptive and cross sectional. Setting: The study was conducted at the Department of Diagnostic Radiology, Fatima Jinnah Medical University/Sir Ganga Ram Hospital, Lahore in collaboration with the Departments of Orthopedics, Neurology, Medicine and Neurosurgery of the same hospital who were referring patients with backache for X-Rays. Duration: Study period was six months from Nov 2015 to April 2016. Sample Size and Selection: First 200 patients referred to Radiology Department during the study period with the presenting complaint of low backache and advised MRI. Sampling Technique: Random/ Non Probability and convenient sampling. Materials and Methods: Patients referred to the Radiology Department for X Ray Lumbosacral spine and MRI. These young adults had presenting complains of with low backache referring to one of the legs, restricted body movements first with activity and later at rest, numbness and foot drop. Bony changes and normal variants such as sacralisation and changes occurring in the visualized spine secondary to this variation were first documented on digital X- Rays taken at right angles to one another mostly as frontal and lateral of the lumbosacral spine. The patients were then referred for MRI Lumbosacral Spine, which confirmed not only the bony but also associated soft tissue abnormalities as well. Results: The results of our study showed that sacralisation is a very common finding and manifests in the form of early degenerative changes in the Lumbosacral spine. Conclusion: Identification of a transitional vertebra is important in young adults as it is a common cause of low backache.